2020
DOI: 10.1002/pc.25884
|View full text |Cite
|
Sign up to set email alerts
|

X‐band dielectric properties of hybrid nanocomposites of nitrogen‐doped carbon nanotube/functionalized nanoclay/polyvinylidene fluoride nanocomposite

Abstract: This study investigates the effect of functionalized nanoclay on dielectric properties in the X‐band (8.2‐12.4 GHz) of synthesized nitrogen‐doped carbon nanotube (N‐CNT)/nanoclay/polyvinylidene fluoride (PVDF) nanocomposites prepared via melt‐mixing. Montmorillonite nanoclay was functionalized by an aminosilane coupling agent, making the nanoclay more compatible with the organic polymer. N‐CNT was synthesized employing a chemical vapor deposition technique. Transmission electron microscopy and optical microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
(130 reference statements)
0
11
0
Order By: Relevance
“…This is also shown by the rheological results (see Figure S3). , However, according to Figure a, with the introduction of only 0.5 wt % of rGO, the electrical conductivity of the PVDF/rGO nanocomposite surged to the conductive region, that is, 6.87 × 10 –3 S/cm. By increasing the loading of rGO nanosheets up to 1 wt %, the network structure was further enhanced, and more conductive paths were formed throughout the PVDF/rGO sample, contributing to the sharp enhancement of the electrical conductivity (1.41 × 10 –2 S/cm).…”
Section: Resultsmentioning
confidence: 98%
“…This is also shown by the rheological results (see Figure S3). , However, according to Figure a, with the introduction of only 0.5 wt % of rGO, the electrical conductivity of the PVDF/rGO nanocomposite surged to the conductive region, that is, 6.87 × 10 –3 S/cm. By increasing the loading of rGO nanosheets up to 1 wt %, the network structure was further enhanced, and more conductive paths were formed throughout the PVDF/rGO sample, contributing to the sharp enhancement of the electrical conductivity (1.41 × 10 –2 S/cm).…”
Section: Resultsmentioning
confidence: 98%
“…The reduction in G ′ is a direct consequence of nanofillers network break up and filler-matrix slippage, leading to a decrease in the number of load-bearing junctions [ 48 , 49 , 50 , 51 , 52 ]. Moreover, it was shown that, for a strong-linked network, the critical strain amplitude decreases to lower values by the introduction of more nanofillers into the polymer media [ 4 , 52 , 53 ]. This is due to the higher sensitivity of the rigid 3D network structure of the nanofillers to the input deformation (i.e., strain amplitude) [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was shown that, for a strong-linked network, the critical strain amplitude decreases to lower values by the introduction of more nanofillers into the polymer media [ 4 , 52 , 53 ]. This is due to the higher sensitivity of the rigid 3D network structure of the nanofillers to the input deformation (i.e., strain amplitude) [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the greater the polarization capacity of the molecules, the greater the dielectric constant of the material. The improvement in nanocomposite dielectric features attributed to the addition of nanoclays depends on the quality and proportion of the nanoclay [27]. The filler is polarized by the introduction of an external electric field, causing a charge disturbance in the nanoclays.…”
Section: Dielectric Constantmentioning
confidence: 99%